2020
DOI: 10.1002/ange.202009490
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Neutral TEMPO Catalysis: Direct Radical (Hetero)Aryl C−H Di‐ and Trifluoromethoxylation

Abstract: Applications of TEMPOC catalysis for the development of redox-neutral transformations are rare. Reported here is the first TEMPOC-catalyzed, redox-neutral CÀH di-and trifluoromethoxylation of (hetero)arenes. The reaction exhibits a broad substrate scope, has high functional-group tolerance, and can be employed for the late-stage functionalization of complex druglike molecules. Kinetic measurements, isolation and resubjection of catalytic intermediates, UV/Vis studies, and DFT calculations support the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Through intermolecular competition experiments employing two electronically diverse arenes, it was found that the * OCF 2 H reacts approximately 3 times faster with toluene than with acetophenone, thereby confirming its electrophilic nature. In a subsequent study, the same group disclosed an innovative redox-neutral process catalyzed by TEMPO, allowing the generation of * OCF 2 H through a redox pathway D. [95] Afterwards, the Prakash group outlined the photoredox-catalyzed (B) difluoromethoxylation of (hetero)arenes using a stable pyridinium reagent 7. [96] Substrate scope: The * OCF 2 H radical is highly electrophilic (ω = 3.39 eV).…”
Section: Difluoromethoxylation (Ocf 2 H)mentioning
confidence: 99%
“…Through intermolecular competition experiments employing two electronically diverse arenes, it was found that the * OCF 2 H reacts approximately 3 times faster with toluene than with acetophenone, thereby confirming its electrophilic nature. In a subsequent study, the same group disclosed an innovative redox-neutral process catalyzed by TEMPO, allowing the generation of * OCF 2 H through a redox pathway D. [95] Afterwards, the Prakash group outlined the photoredox-catalyzed (B) difluoromethoxylation of (hetero)arenes using a stable pyridinium reagent 7. [96] Substrate scope: The * OCF 2 H radical is highly electrophilic (ω = 3.39 eV).…”
Section: Difluoromethoxylation (Ocf 2 H)mentioning
confidence: 99%
“…12 The first TEMPO • -catalyzed, redox-neutral C–H di- and trifluoromethoxylation of (hetero)arenes is reported by Ngai and his research team (Table 1 , J). 13 The oxidation of alcohols to carbonyl compounds with dioxygen was discovered to be facilitated by a new mixture of FeCl 3 , l -valine, and TEMPO. The production of aldehydes and ketones from a variety of primary/secondary benzyl, allylic, and heterocyclic alcohols was accomplished with good to exceptional isolated yields (Table 1 , K).…”
Section: Table 1 Recent Applications Of Tempomentioning
confidence: 99%
“…To produce product 8 in a 70 % isolated yield, the electrochemical trifluoromethoxylation reaction could be stepped up to 3.0 mmol. [119] On the basis of relevant data from earlier research, [120][121][122][123] a possible reaction mechanism was suggested in scheme 7. To Scheme 6.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…On the basis of relevant data from earlier research, [120–123] a possible reaction mechanism was suggested in scheme 7. To create A , HFIP 9 must first bind to the nitrogen atom in 7 .…”
Section: Direct Electrochemical C−h/c−c Bond Oxygenationmentioning
confidence: 99%